PENGARUH PEMBERIAN GEL KOMBINASI EKSTRAK GETAH PEPAYA (Carica papaya L) DAN EKSTRAK DAGING LIDAH BUAYA (Aloe vera) TERHADAP PROSES PENYEMBUHAN ULKUS TRAUMATIKUS PADA MALE WISTAR RATS YANG MENDERITA DIABETES MELITUS - Umi Kulsum; Ratnawati Hendari; Siti Chumaeroh (ODONTO : Dental Journal, 2015)
Introduction: Research on the use of papaya and aloevera sap on wound healing each been done, but effects the combination of the two extracts on wound healing in diabetes mellitus condition has not been done.Purpose: This study aims to determine the effect of a gel combination of papaya latex and aloevera flesh extracts on the traumatics ulcer healing process in diabetic rats.Methods: True experimental laboratory research with the post-test-only control group design that performed on 28 male wistar rats which were divided intofour groups: DM and non-DM rat that treatment with povidone iodine and gel combination of papaya latex and aloevera flesh extract. The treatment was done for 7 days with smearing that was given 2x/day. Traumatics ulcer healing seen from the number of fibroblasts that then were analyzed by One WayAnova and post hoc LSD test.Results: The results showed the number of fibroblasts in DM and non-DM rat with povidone iodine were 44.6 and 42.73; in the DM and non-DM rat with a gel combination of papaya latex and aloe vera flesh extracts were 61.10 and 77.03. One Way Anova test resulted p-value = 0.000, it was mean that there were at least a significant difference on the number of fibroblasts in the two groups. Differences of the number fibroblasts was shown in all groups, except in the group DM and non-DM rats with povidone iodine (p = 0.764).Conclusion: Conclusion of the study was the provision of a gel combination of papaya latex and aloevera flesh extracts effect on the traumatics ulcer healing process in diabetic rats.